Cerebrovascular Events After Transcatheter Aortic Valve Implantation - Armijo, German; Nombela-Franco, Luis; Tirado-Conte, Gabriela (Frontiers in Cardiovascular Medicine, 2018)
Transcatheter aortic valve implantation (TAVI) has emerged as an alternative less invasive treatment for patients with symptomatic severe aortic stenosis. Despite the technological development and knowledge improvement in recent years, neurological complications remain a concern, especially with the expansion of the technique towards younger and lower risk patients. Clinical cerebrovascular events have an important impact on patients´ morbidity and mortality with a multifactorial origin. While cerebral microembolizations during TAVI is a universal phenomenon and embolic protection devices have been developed in an attempt to reduce them, their clinical utility remains unclear. We review the current evidence on cerebrovascular events associated with TAVI and potential preventive strategies.